Investigation of melamine and DOPO-derived flame retardants for the bioplastic cellulose acetate. (October 2020) - Koedel, Justus; Callsen, Christoph; Weise, Markus; Puchtler, Florian; Weidinger, Andy; Altstaedt, Volker; Schobert, Rainer; Biersack, Bernhard
Abstract: In order to identify suitable flame retardant additives for the eco-friendly polymer cellulose acetate (CA), high-melting derivatives of the known flame retardant 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) were combined with the thermoplastic CA and the combustion properties were tested. CA mixtures with bis-phosphonamidates (EDA-DOPO and PIP-DOPO) showed distinct flame retardation effects and a reduction of peak heat release rates (PHRR) by up to 18%. CA mixtures with MDOP, a melamine salt of DOPA (an oxidation product of DOPO), also showed considerable effects and a reduction of PHRR by up to 27%. While producing more smoke than pure CA and CA plus melamine, owing to its aromatic component, MDOP was superior to the CA mixtures with DOPO, EDA-DOPO and PIP-DOPO in this regard. The mixture of CA with melamine gave rise to a distinctly reduced formation of toxic CO and smoke when compared with pure CA. Thus, these additives can be considered for future applications of CA-based polymers with enhanced flame protection. Highlights: Cellulose acetate mixtures with DOPO derivatives showed significantly reduced heat release. Mixtures of cellulose acetate with MDOP showed the lowest heat release. Char formation was observed for mixtures with DOPO derivatives upon combustion. Melamine admixture distinctly reduced CO formation during combustion. Considerable residual masses were observed for mixtures with DOPO derivatives at high temperatures.